Rv2231c, a unique histidinol phosphate aminotransferase from Mycobacterium tuberculosis, supports virulence by inhibiting host-directed defense - Zarin, Sheeba; Shariq, Mohd; Rastogi, Nilisha; Ahuja, Yashika; Manjunath, P.; Alam, Anwar; Hasnain, Seyed Ehtesham; Ehtesham, Nasreen Zafar (Cellular and molecular life sciences : CMLS, 2024)
Nitrogen metabolism of M. tuberculosis is critical for its survival in infected host cells. M. tuberculosis has evolved sophisticated strategies to switch between de novo synthesis and uptake of various amino acids from host cells for metabolic demands. Pyridoxal phosphate-dependent histidinol phosphate aminotransferase-HspAT enzyme is critically required for histidine biosynthesis. HspAT is involved in metabolic synthesis of histidine, phenylalanine, tyrosine, tryptophan, and novobiocin. We showed that M. tuberculosis Rv2231c is a conserved enzyme with HspAT activity. Rv2231c is a monomeric globular protein that contains α-helices and β-sheets. It is a secretory and cell wall-localized protein that regulates critical pathogenic attributes. Rv2231c enhances the survival and virulence of recombinant M. smegmatis in infected RAW264.7 macrophage cells. Rv2231c is recognized by the TLR4 innate immune receptor and modulates the host immune response by suppressing the secretion of the antibacterial pro-inflammatory cytokines TNF, IL-12, and IL-6. It also inhibits the expression of co-stimulatory molecules CD80 and CD86 along with antigen presenting molecule MHC-I on macrophage and suppresses reactive nitrogen species formation, thereby promoting M2 macrophage polarization. Recombinant M. smegmatis expressing Rv2231c inhibited apoptosis in macrophages, promoting efficient bacterial survival and proliferation, thereby increasing virulence. Our results indicate that Rv2231c is a moonlighting protein that regulates multiple functions of M. tuberculosis pathophysiology to increase its virulence. These mechanistic insights can be used to better understand the pathogenesis of M. tuberculosis and to design strategies for tuberculosis mitigation.